Natural Selection on Exonic SNPs Shapes Allelic Expression Imbalance (AEI) Adaptability in Lung Cancer Progression - Huang, Jinfei; Zhang, Yuchao; Ma, Qingyang; Zhang, Yuhang; Wang, Meng; Zhou, You; Xing, Zhihao; Jin, Meiling; Hu, Landian; Kong, Xiangyin (Frontiers in Genetics, 2020)
Tumors are driven by a sequence of genetic and epigenetic alterations. Previous studies have mostly focused on the roles of somatic mutations in tumorigenesis, but how germline variants act is largely unknown. In this study, we screened Single Nucleotide Polymorphisms (SNPs) as a representative of germline mutations. By using RNA sequencing data of lung cancer and paired normal tissues, we analyzed the effects of SNP types, functions and conservativeness on genes with Allele expression imbalance (AEI). We found that natural selection can act on AEI. Functional adaptability of high frequency AEI genes and correlation of AEI incidence with conservativeness were observed in both adjacent tissues and tumor tissues. Moreover, we observed higher AEI incidence of genes with nonsynonymous SNP than those with synonymous SNP. However, we also found that AEI was affected by the allele expression noise, especially in tumor tissues, which led to increased AEI proportion, weakened role of natural selection and disappearance of the influence of SNP types on AEI. We unveiled a previously unknown adaptive regulatory mechanism that natural selection on SNPs can be reflected in allelic expression, which provides insight into better understanding of cancer evolution.